Evaluation of Operational Loading of the Light-Rail Transit (LRT) in Capital Region, Indonesia - Djoko Wahyu Karmiadji; Muchamad Gozali; Anwar Anwar; Hedi Purnomo; Muji Setiyo; Ramli Junid (Universitas Muhammadiyah Magelang, 2020)
In 2015, the Indonesian government issued regulations to accelerate the implementation of integrated Light-Rail Transit (LRT) in the capital region and its surroundings. In order to ensure its operational safety, experimental work is required to test components’ strength of the manufactured LRT structures. Following the JIS 7105 standard test method, the strain and deflection of the structures were measured by vertical load, compression, rotation, and three-point load support test. The critical area estimated in the railroad structure were conducted according to the finite element method, in which strain gauges are installed in areas where the stress concentration exceeds nominal pressure, namely notches, bends, and junction areas. The result shows that the maximum stress on the LRT train structure occurs at the door, where maximum compressive strain value is -1082 Î¼e Â» -75.74 MPa on the left and the maximum tensile strain value is 597 Î¼e Â» 41.79 MPa at the right door. The results of fatigue load analysis represent the average stress (Ïƒm) and voltage amplitude (Ïƒa) at the coordinate system located in the SÃ¸derberg triangle. Meanwhile, the camber value with the full vertical load still has a positive value of 3.03 mm, which indicates a safe limit.